2005
DOI: 10.4049/jimmunol.175.12.7880
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Genes Linked to FcεRI Signaling and to Cytokine and Chemokine Production in Lyn-Deficient Mast Cells

Abstract: Cross-linking the high-affinity IgE receptor, FcεRI, on mast cells activates signaling pathways leading to the release of preformed inflammatory mediators and the production of cytokines and chemokines associated with allergic disorders. Bone marrow-derived mast cells (BMMCs) from Lyn-deficient (Lyn−/−) mice are hyperresponsive to FcεRI cross-linking with multivalent Ag. Previous studies linked the hyperresponsive phenotype in part to increased Fyn kinase activity and reduced SHIP phosphatase activity in the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 47 publications
1
22
1
Order By: Relevance
“…Cytokine production in mast cells as a consequence of Fc RI stimulation seems to be primarily driven by Fyn and not Lyn kinase (23,24). In fact, Fc RI-dependent stimulation of IL-4 production was demonstrated to be defective in Fyn-deficient BMMC but not in Lyn deficiency (23)(24)(25) To determine whether Lyn and/or Fyn might be required for H 2 O 2 -induced IL-4 production, we analyzed IL-4 mRNA up-regulation using BMMC from Lyn Ϫ/Ϫ , Fyn Ϫ/Ϫ , and PI3K Ϫ/Ϫ mice.…”
Section: H 2 O 2 -Induced Il-4 Up-regulation Requires Fynmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokine production in mast cells as a consequence of Fc RI stimulation seems to be primarily driven by Fyn and not Lyn kinase (23,24). In fact, Fc RI-dependent stimulation of IL-4 production was demonstrated to be defective in Fyn-deficient BMMC but not in Lyn deficiency (23)(24)(25) To determine whether Lyn and/or Fyn might be required for H 2 O 2 -induced IL-4 production, we analyzed IL-4 mRNA up-regulation using BMMC from Lyn Ϫ/Ϫ , Fyn Ϫ/Ϫ , and PI3K Ϫ/Ϫ mice.…”
Section: H 2 O 2 -Induced Il-4 Up-regulation Requires Fynmentioning
confidence: 99%
“…In fact, Fc RI-dependent stimulation of IL-4 production was demonstrated to be defective in Fyn-deficient BMMC but not in Lyn deficiency (23)(24)(25) To determine whether Lyn and/or Fyn might be required for H 2 O 2 -induced IL-4 production, we analyzed IL-4 mRNA up-regulation using BMMC from Lyn Ϫ/Ϫ , Fyn Ϫ/Ϫ , and PI3K Ϫ/Ϫ mice. BMMC from wild type, Lyn-, Fyn-, and PI3K-null mice were treated with 10 nM H 2 O 2 for 3 h and then analyzed together with untreated samples for IL-4 mRNA production.…”
Section: H 2 O 2 -Induced Il-4 Up-regulation Requires Fynmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) and microarray analysis of various sources of MC RNA for R4 RGS family members revealed expression of Rgs1, 8,13,16 13 and 18 (data not shown). We focused on Rgs13 because microarray studies of purified human cell subsets showed restricted RGS13 expression in MCs compared to other hematopoietic cells (Fig.…”
Section: Enrichment Of Rgs13 In Mcsmentioning
confidence: 99%
“…RGS isoforms can be further divided into subfamilies on the basis of additional protein interaction motifs. However, the R4 subfamily of 8,13,16,18,and 21) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation